2004
DOI: 10.1111/j.1365-2222.2004.01994.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic use in the first year of life and asthma in early childhood

Abstract: After adjusting for sex and illnesses of the lower respiratory tract (LRIs), we found a significant association between antibiotic use in the first year of life and asthma between the ages of 1 and 2 years (odds ratio (OR) for 1-2 vs. no courses of antibiotics=1.9, 95% confidence interval (CI)=1.3-2.7; OR for 3-4 vs. no courses of antibiotics=1.6, 95% CI=1.1-2.4; OR for at least 5 vs. no courses of antibiotics=2.1, 95% CI=1.5-3.2). After adjustment for sex and LRIs in the first year of life, there was no signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(86 citation statements)
references
References 19 publications
4
81
0
1
Order By: Relevance
“…In any case, this is a topic which warrants further investigation. Regardless of the extent to which factors other than antibiotic administration influence these results, there is a concern that these short-term changes to the microbiota may in turn have long-term health consequences in the form of allergies, asthma, and obesity later in life (4,13,25). While follow-up analysis of these infants was outside the scope of this short-term study, we hope to return to this topic in future studies.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In any case, this is a topic which warrants further investigation. Regardless of the extent to which factors other than antibiotic administration influence these results, there is a concern that these short-term changes to the microbiota may in turn have long-term health consequences in the form of allergies, asthma, and obesity later in life (4,13,25). While follow-up analysis of these infants was outside the scope of this short-term study, we hope to return to this topic in future studies.…”
Section: Discussionmentioning
confidence: 96%
“…Short-term health effects include antibiotic-associated diarrhea, gastrointestinal discomfort, gastritis, and glossitis (24) as well as the possible development of antibiotic-resistant bacterial populations in the gut (39). Furthermore, it has been suggested that a number of longterm health effects are influenced by the development of the gut microbiota (38) and, in turn, the immune system in early life (32,33,37,64), with data suggesting that antibiotic administration contributes to the risk of developing asthma and allergy (13,25,40) in addition to heightened risk of obesity (4) later in life. The risks associated with disrupting the gut microbiota may be especially great in young infants, as antibiotic administration can impact the commensal microbiota at a time when this population is in rapid flux and can easily be unbalanced.…”
Section: Discussionmentioning
confidence: 99%
“…In seven of these 21 studies wheeze or asthma were not associated with antibiotic use [31][32][33][34][35][36][37], so that bias deriving from RC and CbI was not of concern. We will go on to discuss the remaining 14 studies with regard to RC and CbI.…”
Section: Systematic Reviewmentioning
confidence: 98%
“…Six studies had follow-up periods until 4-5 yrs of age [3,32,34,35,43,46,] of which one focused on recurrent wheeze [32] and the remaining five were based on the outcome ''asthma'' using various definitions [3,34,35,43,46]. It has to be kept in mind that a diagnosis of asthma in pre-school children is difficult to establish, as it often cannot be distinguished from infectionrelated wheeze.…”
Section: Outcome Definitionmentioning
confidence: 99%
“…525 Intake of the analgesic, paracetamol (acetaminophen), may be associated with asthma in both children and adults, 526 although exposure during infancy may be confounded by use of paracetamol for respiratory tract infections. 526 Frequent use of paracetamol by pregnant women has been associated with asthma in their children.…”
Section: Medications and Other Factorsmentioning
confidence: 99%